2004
DOI: 10.1080/0267303042000204287
|View full text |Cite
|
Sign up to set email alerts
|

The uneven geography of housing affordability stress in Canadian metropolitan areas

Abstract: Housing in-affordability is a growing problem within Canadian urban areas. This research asks an as-yet unanswered spatial question: where do those suffering high rates of housing affordability stress reside and what do the spatial patterns imply about policies intended to address this housing problem? This paper tabulates and maps the spatial distribution of households that pay excessive amounts of their income for rent in order to identify locations within metropolitan regions where housing affordability str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 35 publications
0
68
0
1
Order By: Relevance
“…The costs of housing can be a major burden, and the pattern of housing costs vis-à-vis household income merits and has received in-depth study as a topic in itself (see for example Bunting et al 2004;Fahey 2004). Here our focus is on situations where housing costs are problematic as a distinct aspect of housing-related deprivation, and to capture this we constructed an index based on responses to two questions in the survey:…”
Section: Housing Costs Problemsmentioning
confidence: 99%
“…The costs of housing can be a major burden, and the pattern of housing costs vis-à-vis household income merits and has received in-depth study as a topic in itself (see for example Bunting et al 2004;Fahey 2004). Here our focus is on situations where housing costs are problematic as a distinct aspect of housing-related deprivation, and to capture this we constructed an index based on responses to two questions in the survey:…”
Section: Housing Costs Problemsmentioning
confidence: 99%
“…Perhaps the most interesting result is the groups for which there are only small differences across cities. For the Whites and the Chinese, only Montreal and other CMAs are significantly different from the reference group; for the Canadian-born, there are no significant differences between CMAs whatsoever, even though others have found that city differences matter in other contexts (Bunting et al 2004;Skaburskis 2004).…”
Section: Resultsmentioning
confidence: 88%
“…Access to social housing stock particularly by low income immigrant households has enormous influence on housing experience of immigrants (Carter et al 2009). Therefore, the reduction in social housing stock over the decades has pushed low income earners including refugees and immigrants into the housing markets where prices are determined by market forces (Skaburskis and Mok 2000;Bunting et al 2004;Murdie 2008). A recent study by Simone and Newbold (2014), suggests that overpriced housing markets in the most popular immigrant destinations in Canada (Montreal, Vancouver and Toronto) makes homeownership difficult.…”
Section: Understanding Immigrant Housing Trajectoriesmentioning
confidence: 95%